Molecular identification of Audouinella-like species (Rhodophyta) from China based on three short DNA fragments - Nan, Fangru; Feng, Jia; Han, Xiaojing; Lv, Junping; Liu, Qi; Xie, Shulian (Phytotaxa, 2016)
Four algal specimens with morphological resemblance to Audouinella were collected in China, both bluish and reddish thalli included. Because of the taxonomic obscurity of the acrochaetioid lineage, a molecular phylogenetic analysis was performed to verify the phylogenetic position of these specimens based on three short DNA fragments including psbA, UPA and COI-5P. Molecular sequences were analyzed by neighbor-joining, maximum likelihood, Bayesian, and NeighborNet methods. Phylogenetic relationships based on three DNA fragments were consistent in that the four Audouinella-like thalli clustered together with Thorea hispida (Thore) Desvaux with strong support. The four specimens morphologically similar to Audouinella were concluded to represent the chantransia stage of Thoreales based on molecular trees. The reddish specimen shared no sequence divergence with the bluish ones. For identification of freshwater Audouinellla, criteria of thallus color must be used with caution and molecular tool-assisted analysis are essential. The formerly established new species Audouinella heterospora S.L.Xie & Y.J.Ling was inferred to be synonymous with the chantransia stage of T. hispida. The three DNA molecular markers demonstrated to be effective to ascertain the phylogenetic position of acrochaetioid algae specimens, and to delineate other freshwater Rhodophyta.